2014
DOI: 10.2106/jbjs.l.01430
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Career Choice in Academic Medicine Among Orthopaedic Surgery Residents

Abstract: In 2013, 1038 applicants, 833 of whom were U.S. graduates, applied for 693 orthopaedic residency spots. Orthopaedic residency program directors thoroughly screen applicant data, selecting those applicants who will be most successful during the residency. Although the most important consideration for program directors is choosing residents who will obtain competence and will pass the orthopaedic board examinations, many applicants are chosen also for their ability to contribute to the field through leadership, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…Fan et al's study looked at 60 orthopedic resident graduates, exploring the factors of clerkship honors, Step 1 score, Step 2 score, number of publications prior to residency, number of publications during residency, Alpha Omega Alpha (AOA) honor society membership, additional doctorates or masters degrees, and orthopedic board examination scores in relationship to academic career. They found that the residents who went into academics had, on average, 2.36 publications compared to 0.38 publications for those who went into non-academic careers (p = 0.019) [1].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Fan et al's study looked at 60 orthopedic resident graduates, exploring the factors of clerkship honors, Step 1 score, Step 2 score, number of publications prior to residency, number of publications during residency, Alpha Omega Alpha (AOA) honor society membership, additional doctorates or masters degrees, and orthopedic board examination scores in relationship to academic career. They found that the residents who went into academics had, on average, 2.36 publications compared to 0.38 publications for those who went into non-academic careers (p = 0.019) [1].…”
Section: Discussionmentioning
confidence: 98%
“…Their research and accomplishments promote novel and improved treatments and procedures, as well as discoveries for both common and rare diseases, thereby improving the health and care of their patients. There are many factors that go into choosing between an academic versus a non-academic medical career [1,2]. A previous study of radiation oncology physicians has shown that they are twice as likely to choose an academic career if they had published at least one peer-reviewed paper during medical school [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al reported that; completion of a research fellowship, graduation from a top-20 medical school, and desire to become an academic surgeon were mostly associated with the choice of academic career 2 . Fan et al investigated the academic career of their department's past residents via "Google", and authors observed that orthopedics residents choosing academic career had increased number of publications during residency 3 . In their study, Ahn et al sent a survey to orthopedics and traumatology residents and chairs about future research activity; the authors found that having primary authorship of a study was the main predictive of future research activity 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Several factors influencing the decision for academic career after graduation have been investigated previously in the literature [2][3][4] . However, no study could be found reporting the effect of the training centre on the future academic career of orthopedic residents.…”
Section: Introductionmentioning
confidence: 99%